Journey of Commitment: Sustaining Marriage for 25 Years and Beyond - Zapanta-Ribu, Mary Shaira Christa P.; Ribu, Gene Louise V. (Future Science / FSH-PH Publications, 2025)
This study investigated the long-term sustainability of marriage in the Philippines, addressing a gap in local research on couples married for 25 years or more. Using a qualitative design with purposive sampling, interviews were conducted with five long-married Filipino couples (ten participants) to explore their reasons for marrying, their definition of marriage, the secrets to their longevity, and their marital satisfaction. Results demonstrate that the endurance of these unions is rooted in three key themes: commitment, tradition, and mutual reliance. The initial decision to marry was driven by love and the traditional desire to build a family before cohabitation. Participants uniformly defined marriage as a sacred, lifelong covenant and a commitment. The essential ingredients for sustaining high satisfaction were consistently identified as open communication, reciprocal respect, mutual support, and persistent effort. The study concludes that intentional commitment and the adherence to traditional family values are indispensable factors for the long-term survival and stability of these Filipino partnerships, despite shifting societal views.